2019
DOI: 10.1210/clinem/dgz063
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Environmental Disruptors and Sexually Dimorphic Changes in Maternal and Neonatal Oxidative Stress

Abstract: Context Early pregnancy exposure to endocrine disrupting chemicals (EDCs) may contribute to poor birth outcomes through oxidative stress (OS)-mediated disruption of the maternal and fetal milieu. Most studies have investigated the effect of single EDC exposures on OS. Objective Assess the association of uniquely weighted mixtures of early pregnancy exposures with the maternal and neonatal OS markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 77 publications
2
15
0
Order By: Relevance
“…2020 ). Consistent with our findings, adjusted linear regression models in the prospective analyses of that study reported a negative association between first-trimester maternal urinary Pb and neonatal cord blood CY ( Puttabyatappa et al. 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…2020 ). Consistent with our findings, adjusted linear regression models in the prospective analyses of that study reported a negative association between first-trimester maternal urinary Pb and neonatal cord blood CY ( Puttabyatappa et al. 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…2019 ). However, their findings for first-trimester urinary phthalate metabolites in adjusted linear regression models were less consistent, where inverse cross-sectional associations were observed between two metabolites (MCPP and MCINP) and the first-trimester maternal plasma CY level ( Puttabyatappa et al. 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Demographics, obstetric history, perinatal data, delivery, and newborn outcomes were recorded by two trained research obstetricians from Fuzhou Maternal And Child Health Care System. Maternal serum Hcy levels at the first trimester (the first prenatal appointment between 8-12 weeks), the second trimester (24)(25)(26)(27)(28) weeks), and the third trimester (admission to the hospital for delivery) were recorded.…”
Section: Study Population Samplementioning
confidence: 99%